Aging and Feminization: Implications for Future Travel Demands of the Elderly - Brigitte Waldorf; David Pitfield (European Regional Science Association (ERSA), 2003)
An increasing proportion of the oldest-old (85+) population, combined with a pronounced abundance of older women relative to older men, characterize the demographic development of industrialized countries. Both, aging and feminization, strongly influence the transportation demands of the future. As people age, their driving abilities diminish, leading to driving reduction and ultimately driving cessation. Moreover, the literature suggests that the driving adjustments operate differently for men and women. Especially, women are prone to cease driving at an earlier age than men, and thus are in need of travel modes other than driving at an earlier age. This paper therefore aims at estimating the demand for non-automobile based mobility of the elderly. Towards that end, it develops a multi-risk survival model that links the demographic shifts towards a growing elderly population and towards the feminization of the older population with driving cessations rates. The model is used to simulate the future demand for non-automobile based mobility of the elderly, as well as estimates of older men's and women's expected number of years without driving a car. Preliminary results for The Netherlands and the U.S. suggest that, while women's conditional life expectancies are substantially higher than those of men, there is barely any difference between men's and women's expected number of years without driving a car. Moreover, in the Netherlands, demand growth rates will exceed the growth rates of the elderly population over the next 15 years. In the U.S., in contrast, excessive demand growth rates will occur substantially later, when the huge baby boom has reached the oldest age cohorts. The paper concludes with a discussion of policies and planning strategies needed to respond to the mobility needs of the elderly following driving reduction and driving cessation.
Keywords: 330